Theoretical aspects of empirical research consumption of goods – the effect of emotions on the attitude to brand - Skryhun, Natalya; Maksymova, Yelizaveta; Boyko, Irina (My University, 2019)
Identified theoretical features of empirical research, the emotional attitude to the products of the brand and the importance of past consumption experience for the marketing of the enterprise are considered. The main elements and values of the marketing impact of empirical research on the consumer, as well as their research methods, are highlighted.
Keywords: споживчі вимоги; consumer satisfaction; product brand; ринок покупця; поведінка споживачів; задоволеність споживачів; бренд товару; кафедра маркетингу; кафедра економіки праці та менеджменту